1991
DOI: 10.1063/1.1142145
|View full text |Cite
|
Sign up to set email alerts
|

Hardware and software corrections of the spatial distortions of position-sensitive detectors

Abstract: Possible causes of the spatial distortion encountered when using pierced resistive anodes for position-sensitive detection are discussed. An accurate map of the spatial distortion around a circular hole in a resistive anode is presented, which shows that the hole's effect is felt at distances up to three times its radius. The effect of load conditions on the detector's spatial linearity, as well as the distortions induced near the center of the detector due to penetrating electrostatic fields, are also discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Previous efforts to measure strains accurately using a 2D area detector showed that good calibration of the experimental geometry and distortion are essential [10]. The conventional methods [11][12][13][14][15] for calibration of earlier CCD detectors generally fitted smooth functions (splines or polynomials) to images of grid-like targets. The production of an accurate calibration artifact is problematic because machining tolerances are difficult to reduce below about 10 µm for a >150-mm-sized object.…”
Section: Introductionmentioning
confidence: 99%
“…Previous efforts to measure strains accurately using a 2D area detector showed that good calibration of the experimental geometry and distortion are essential [10]. The conventional methods [11][12][13][14][15] for calibration of earlier CCD detectors generally fitted smooth functions (splines or polynomials) to images of grid-like targets. The production of an accurate calibration artifact is problematic because machining tolerances are difficult to reduce below about 10 µm for a >150-mm-sized object.…”
Section: Introductionmentioning
confidence: 99%